Microbiological quality of poultry food and water used in chicken breeding farm in the peri-urban area of Bamako, Mali - Toure, H.; Ouattara , M.; Traoré , M.; Babana , A.; Camara , M.; Coulibaly , M.; Maiga, A.; S., Kéita; Traoré, A. S.; Touré, I.; et al. (Advances in Social Sciences Research Journal, 2020)
The peri-urban area of Bamako contains many chicken breeding production farms. The conditions of these farms can constitute risk factors. The insufficiency of scientific data relating to the environment of those farms and to the various inputs makes it difficult to determine their real impact on the sanitary quality of food. Our study aimed to assess the microbiological quality of the food and water used in 15 farms in the peri-urban area of Bamako. The results showed that all of the analyzed water samples had more or less aflatoxin content with a maximum value of 12.2 ppb observed on the Bamako-Tienfala axis. The presence of mould was also detected in 46.6% of the water samples analyzed with a higher frequency in well water, i.e. 26.66%. Salmonella contamination of water has been observed in samples taken on all axes, with a strong dominance on the Bamako-Kati axis. For poultry foods the samples taken from farms on the Bamako-Kassela and Bamako-Siby axes were positive. Poultry food and water used in chicken breeding production are risk factors identified in the production system.